PENERAPAN ALGORITMA GENETIKA UNTUK MEMAKSIMALKAN LABA PRODUKSI JILBAB - Samaher .; Wayan Firdaus Mahmudy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2015)
A maximum profit is the main goal of each production processes in industry. However, the profit is limited by the availability of production material and investment fund. The producer should determine the volume of each product types (hijab) to get a maximum profit while considering various production constraints. This study proposes genetic algorithm to obtain an appropriate production volume. Computational experiments are conducted to get the best parameters for the genetic algorithm. By using the best parameters, the proposed algorithm results the combination of product types that should be produced with maximum profit and lowest constraints violation.